SYMBOL AND MYSTERY - Amaladoss, M. (Journal of Dharma, 1977)
Tremendum et Jascinans-this celebrated phrase of Rudolf Otto sums up admirably our normal reaction in the presence of Mystery. On the one hand it seems profound, transcendent, beyond the reach of ordinary experience, unknown and unknowable. One is reduced to wordless wonder before it, unable to say anything more than neti neti=-oox thus, not thus. Face to face with the mysterious Absolute, even the words of Sruti can only be relative, inadequate and provisional. The Mystery is tremendum, But this same Mystery is also very dangerously attractive-fascinans. One experiences in oneself a deep desire to experience that. One seems to have a fleeting glimpse of it now and then. Its power is sensed to be active in human life and history. More has been written about it than about anything else. Taking these two aspects together, Mystery seems to be something we are constantly approaching and which, all the time, keeps eluding our grasp.